Comparison of TLR-2, TLR-4, and antimicrobial peptide levels in different lesions of acne vulgaris. (1st October 2016) - Ozlu, Emin; Karadag, Ayse Serap; Ozkanli, Seyma; Oguztuzun, Serpil; Kilic, Murat; Zemheri, Ebru; Akbulak, Ozge; Akdeniz, Necmettin
Abstract: Context : Recent studies have shown that tolls like receptors (TLRs) and antimicrobial peptides (hBD-1, cathelicidin) play an important role in the pathogenesis of acne vulgaris (AV). Objective : To evaluate and report the expression of TLR-2, TLR-4, hBD-1 and cathelicidin in different regions of skin in AV. Participants : This study was performed in 80 patients with AV and a control group of 20 healthy individuals. Material and methods : Skin biopsies were performed from 20 papular, 20 pustular, 20 comedonal and 20 nodular lesions of patients and 20 healthy volunteers. Expression levels of TLR-2, TLR-4, hBD-1 and cathelicidin in four separate areas (epidermis, dermis, inflammation region and skin appendages) were evaluated by immunohistochemical method. Further, these parameters were compared between different skin lesions. Results : A significant difference was found between the levels of staining of TLR-2, TLR-4 and hBD-1 from the epidermis, inflammation region, dermis and skin appendages ( p  < 0.05). Levels of cathelicidin were different in only the inflammation region ( p  < 0.05). The level of TLR-2 in the epidermis with nodules was lower than the papules and comedones ( p  < 0.05). Levels of TLR-2 in the inflammation and dermis of the cases with papules were significantly higher when compared to pustules ( p  < 0.05). The levels of staining of TLR-4 in the dermis with comedones were significantly lower compared to the cases with papules ( p  < 005). The level of hBD-1 in the epidermis region of comedones was significantly higher compared to nodules ( p  < 0.05). The expression of cathelicidin in the inflammation region of comedones was significantly low ( p  < 0.05). Conclusion : It is thought that TLR-2, TLR-4, hBD-1 and cathelicidin play an important role in the pathogenesis of AV and in the development of different acne types. We think that, better results could be obtained in treatment of AV with different treatment options targeted in regulation of TLR-2, TLR-4, hBD-1 and cathelicidin release.